OPTIMALISASI GERAKAN LITERASI PADA SANTRI DI PONDOK PESANTREN ITTIHADUL UMMAH - risma, kharisma nurul fauziah (Pondok Jurnal-LP2M STAI Darul Kamal, 2021)
Currently, the awareness of the importance of literacy among young people is very low. Whereas literacy is the ability to read and write. All knowledge can be known and even obtained by literacy. Literacy is a process of interaction or an ability within a person. Various readings that are now easy to access such as books, PDFs, journals, online libraries, and various other media are not able to arouse interest in reading, one of which is in Islamic boarding schools. The lack of available facilities is a major problem for all students at the Ittihadul Ummah Islamic Boarding School, especially among senior students. And in the end it causes enthusiasm or interest in reading students to decrease. This service activity with the Ulya santri literacy movement program at the Ittihadul Ummah Islamic Boarding School was carried out with the aim that all Ulya students were enthusiastic in literacy and could create works that could be seen by the general public. The approach method used is ABCD, which is an approach model by finding and utilizing the assets owned by the main target of the work program, namely Pondok Pesantren Ittihadul Ummah. The implementation of the work plan or program at the Ittihadul Ummah Islamic Boarding School, Banyudono Ponorogo was carried out well and smoothly according to the method used.